PENGEMBANGAN BUKU PENGASUHAN BERBAHASA DALAM MENSTIMULASI KESANTUNAN INTERAKSI PENGASUHAN ANAK-ANAK USIA PRASEKOLAH (Universitas Negeri Semarang, 2013)
The statements of this study are: how the need, characteristic, principles, draft, scoring, and effectiness of language care book package. This study belongs to development study. The instrument used were: the observation guideline, interview guideline, questionnaire, and experts’ scoring instrument. Based on the need analysis, the characteristics of teachers’ speech act viewed from its politeness degree belongs to polite category for all kinds of speech act. In other hand, the teachers’ need in supplying language care book focused on the need of care process, whether planning, implementing, and evaluating. As a stepping stone to create product draft, the characteristics of language book in market analyzed. The principles of book development contains: organizing, material, material presentation, language and literacy, graph, and teachers’ activity guideline. The draft of language care book developed in the form of package containing children’s book, teacher’s guidance book, and CD of learning guidance. After teachers’ and experts’ understanding tests were done, it can be stated that the product draft has been good and appropriate as a medium or learning source in children’s care interaction. After that, based on the result of product effectiveness test in learning, the package is effective and it can improve students’ communicative competence.